Analisis Kepercayaan Diri Anak Melalui Pembelajaran Seni Tari Kreasi Usia 5-6 Tahun di TK Petro Medan Perjuangan - Asido Theresia Sihite; Elya Siska Anggraini (Khirani: Jurnal Pendidikan Anak Usia Dini, 2024)
This research is a qualitative study which aims to describe the self-confidence of children aged 5-6 years at Perjuangan Kindergarten through learning the art of creative dance. Self-confidence is a person's positive attitude that enables him to develop a positive assessment of himself and the environment he faces. Creative dance learning is a form of performing art where children create their own movements and expressions based on a certain theme, concept or inspiration. This research uses observation, interview and documentation data collection techniques. The subjects in this study were 11 children in group B and teachers in class B. The results of this study showed that building self-confidence in children through the art of dance, teachers used several methods, namely, using a demonstration method approach, providing positive encouragement so that children felt comfortable. , maintaining open communication with children, providing motivation and praise, and helping children when they have difficulties.